Construction and disillusionment of the cultural Utopia of Huang Ya - Chan, Mee Yoke (2019)
After the World War II, the civil war broke out between the Chinese Nationalist Party (Kuomintang) and the Communist Party of China （ CPC). Subsequently, a great number of intellectuals who supported Kuomintang and the Third Force decided to leave Hong Kong in the hope of rebuilding the traditional culture which was destroyed by the Communist Party of China. Some of them worked in Hong Kong press company to promote the Chinese culture, some engaged in media printing and publishing of student and youth magazines with financial support from the United States Information Agency (USIA). Thereafter, Union Press in Hong Kong set up branches in Singapore to publish the Chao Foon and Student Weekly literary magazines, with the intention to develop Chinese traditional culture and provide the youth in Malaya and Singapore with different kinds of reading materials. In the 50s (1959), Huang Ya arrived Malaya after Shen Qing, Yao Tuo, Fang Tian and Huang Sicheng. He worked as an editor for Chao Foon and Student Weekly in Kuala Lumpur. Huang Ya was born in Xiamen, China. Due to the changes in mainland political situation, he exiled to Hong Kong in 1950 and worked in Union Press. During the first 10 years in Malaya (1959 – 1969), he showed a great interest in the development of Mahua literary and cultural activities, and also actively advocated the writing of modernist literature among the youth writers. In the early 60s, besides putting effort in publishing youth magazines, such as Hai Tian, Huang Yuan and Xin Chao in peninsula of Malaya, Huang Ya took a great initiative to promote the development of Malaysian Chinese Literature. Moreover, his dedication in establishing literary groups and publishers shows his great ambition of building up an Utopia of culture. In this thesis, I try to study the various cultural activities promoted by Huang Ya while constructing Utopia culture in Malaya , from beginning until the end , and how does it influence the generation of Chinese youth writers in Malaya, and affirm his contribution to Mahua Literary.